Otomatisasi Pengukur Suhu Badan dan Penyemprotan Hand Sanitizer Menggunakan Sensor Suhu dan Ultrasonik Berbasis Arduino Uno - Emerensiana Ngaga; Dior Yosua Christi K.C; Emiliana M. Meolbatak (Puslitbang Sekawan Institute Nusa Tenggara, 2022)
The Corona virus today has spread throughout Indonesia. In an effort to prevent it, almost every place does a body temperature check, sprays hand sanitizer or washes hands but is still manual in which it requires officers to measure body temperature and spraying hand sanitizer or hand washing activities in public places that are used together which can be a source of viral dissemination. To minimize direct contact with objects used in general and to displace the role of officers in checking body temperature and spraying hand sanitizer, it is necessary to make a tool or robot that can measure body temperature and spray hand sanitizer that works automatically. This robot uses ultrasonic sensors as an object detectors, the temperature sensors for body temperature detector and the Arduino Uno as controller. Output uses a Relay module that is connected to the servo motor that sprays hand sanitizer through a small hose. These tool are considered effective in detecting objects in the sensor area. With this tool, it can replace the role of officers in measuring body temperature and spraying hand sanitizers so as to minimize direct contact with objects that are used in general so as to prevent the spread of the Corona virus.